Sociological and Marxist Analysis of Surveillance in the Process Leading to Data Surveillance - AL, EYÜP (My University, 2022)
The aim of this study is to expose data surveillance to sociological and Marxist analysis by revealing different stages of surveillance from past to present. Social outcomes of surveillance with sociological analysis, economic and political reasons of surveillance with Marxist analysis are discussed. However, it is claimed that the modern structure of surveillance has been opened to discussion, and its digitalization and fluidization have given birth to data surveillance as a new surveillance and control form. Therefore, the classical surveillance conditions defined around Bentham’s idea of “Panopticon” and Foucault’s texts have changed a lot. Since this change is not only structural, the stages of the surveillance mechanism and its aims in the historical process are open to discussion. In the contemporary period, surveillance has also transformed at a point where speed and flexibility determine all kinds of everyday actions. In order to understand this transformation, this article examines how surveillance reaches a more fluid and mobile form, and the actions performed in digital environments are followed on the data axis instead of tracking the body. As a result, it is concluded that the forms of surveillance move away from oppression, individuals are included in surveillance voluntarily, data surveillance is used for economic and political interests, and data provides much more efficient, individual and instant information without any time and place limits. Keywords: Panopticon, Surveillance, Information Technologies, Data Surveillance, Sociological and Marxist Analysis

Bu çalışmanın amacı geçmişten günümüze gözetimin değişik safhalarını ortaya koyarak veri gözetimini sosyolojik ve Marksist analize tabi tutmaktır. Sosyolojik analiz ile gözetimin sosyal çıktıları, Marksist analiz ile gözetimin ekonomik ve politik nedenleri ele alınmaktadır. Bununla birlikte gözetimin çağdaş yapılanması tartışmaya açılarak dijitalleşmesinin ve akışkan bir hal almasının yeni bir gözetleme ve denetleme biçimi olarak veri gözetimini doğurduğu iddia edilmektedir. Dolaysıyla Bentham’ın “Panoptikon” fikri ile Foucault’nun metinleri etrafında tanımlanan klasik gözetleme koşulları fazlasıyla değişmiştir. Bu değişim sadece yapısal olmadığı için gözetim mekanizmasının ve amaçlarının tarihsel süreçte hangi aşamalardan geçtiği tartışmaya açılmaktadır. Çağdaş dönemde hızın ve esnekliğin her türlü gündelik eylemi belirlediği bir noktada gözetim de dönüşmektedir. Bu dönüşümü anlayabilmek için makalede gözetimin nasıl daha akışkan ve hareketli bir forma ulaştığı, beden yerine dijital ortamlardaki eylemlerin takibinin veri ekseninde gerçekleştirildiği incelenmektedir. Sonuç olarak gözetleme biçimlerinin baskıdan uzaklaştığı, bireylerin gönüllü olarak gözetime dahil edildiği, veri gözetiminin ekonomik ve politik çıkarlar için kullanıldığı, verinin herhangi bir zaman ve mekân sınırına takılmaksızın çok daha verimli, bireysel ve anlık enformasyon sunduğu görülmektedir. Anahtar Kelimeler: Panoptikon, Gözetim, Enformasyon Teknolojileri, Veri Gözetimi, Sosyolojik ve Marksist Analiz
Veri Gözetimine Giden Süreçte Gözetimin Sosyolojik ve Marksist Analizi
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Sociology; Mass Communications and Mass Media; İLETİŞİM; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); COMMUNICATION; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); İletişim; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Communication; General Social Sciences; Social Sciences & Humanities; Panopticon; Surveillance; Information Technologies; Data Surveillance; Sociological and Marxist Analysis; MEDIA; : Panoptikon; Gözetim; Enformasyon Teknolojileri; Veri Gözetimi; Sosyolojik ve Marksist Analiz; Panopticon; Surveillance; Information Technologies; Data Surveillance; Sociological and Marxist Analysis